Oblique line contrast: A new radiomorphometric index for assessing bone quality in dental panoramic radiographs - Plauto Christopher Aranha Watanabe; Leonardo Ferreira Machado; Giovani Antonio Rodrigues; Alan Grupioni Lourenço; Matheus Arazin Bitencourt; Rodolfo Maestrello Zerbato (Heliyon, 2022)
The present study was carried out to assess the possible changes in mandibular bone density according to age and gender through dental panoramic radiographs (PAN). More specifically, the region of the mandibular oblique line. Materials & methods: A group of 374 dental patients previously treated in the Ribeirão Preto Dental School (FORP/USP) was included in the study. The complete dental profiling of all the subjects (including PAN images) was previously available in the archive of the same institution. Those subjects were separated into four groups considering age and gender: Group 1–100 young adult men (21.48 ± 3.34 y. o.), Group 2–100 young adult women (20.66 ± 1.52 y. o.), Group 3–87 postmenopausal women (74.07 ± 9.82 y. o.), and Group 4–87 men over 70 years old (75.92 ± 8.71 y. o.). A new index called “W-index” (WI) was proposed for analyzing the possible difference in mandibular bone density. This new index is the ratio between the average pixel value of the image area of the mandibular ramus (AVMR) and the average pixel value of the image area of the mandibular oblique line (AVOL) (WI = AVMR/AVOL). WI was measured for each subject on each PAN and statistical analysis was performed to search how well WI can characterize each study group. Results: The largest difference in WI is observed when we compare older subjects (WI 0.73 ± 0.11) with younger subjects (0.89 ± 0.05). WI also varies significantly with gender but in a smaller amount. Mean WI for old women (0.68 ± 0.11) was found lower than for old men (0.77 ± 0.09), and mean WI for young women (0.89 ± 0.05) was also inferior to young men (0.91 ± 0.05). The differences in WI observed in the subject group were tested for a significance level of α = 0,01. We speculate that WI refers to an aspect of bone mineral density. First, the sharp contrast of the mandibular oblique line may signify the loss of mandibular bone mass. And second, it showed to vary significantly with gender and age, but with higher intensity with age. Clinical significance: WI might be used in the future for low bone mineral density risk assessment.